2014
DOI: 10.1017/jfm.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Bubbling reduces intermittency in turbulent thermal convection

Abstract: Intermittency effects are numerically studied in turbulent bubbling Rayleigh-Bénard (RB) flow and compared to the standard RB case. The vapour bubbles are modelled with a Euler-Lagrangian scheme and are two-way coupled to the flow and temperature fields, both mechanically and thermally. To quantify the degree of intermittency we use probability density functions, structure functions, extended self-similarity (ESS) and generalized extended self-similarity (GESS) for both temperature and velocity differences. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 51 publications
7
28
1
Order By: Relevance
“…For small values of the coupling parameter k, the chaotic regime is asynchronous; that is, ̸ = . Transition from asynchronous to synchronous generation occurs through the intermittency of "bubbling" type [28,29]. Figure 14 shows that the variation of the control parameters allows different behaviors which are periodic or chaotic behavior.…”
Section: Remarkmentioning
confidence: 99%
“…For small values of the coupling parameter k, the chaotic regime is asynchronous; that is, ̸ = . Transition from asynchronous to synchronous generation occurs through the intermittency of "bubbling" type [28,29]. Figure 14 shows that the variation of the control parameters allows different behaviors which are periodic or chaotic behavior.…”
Section: Remarkmentioning
confidence: 99%
“…The studies of Lakkaraju et al (2011Lakkaraju et al ( , 2013, Lakkaraju, Toschi & Lohse (2014) and Oresta et al (2009) focus on the modification of the Rayleigh-Bénard convection by a disperse vapour bubble phase. Lakkaraju et al (2011) in particular identified two opposite effects: on the one hand, the latent heat of vapour tends to decrease the temperature variance, which should reduce convection; on the other hand, the bubble growth due to the heat absorption causes additional buoyancy effects and agitation sources.…”
Section: Introductionmentioning
confidence: 99%
“…Lakkaraju et al (2011) in particular identified two opposite effects: on the one hand, the latent heat of vapour tends to decrease the temperature variance, which should reduce convection; on the other hand, the bubble growth due to the heat absorption causes additional buoyancy effects and agitation sources. The presence of the vapour bubbles was found to drastically reduce the intermittency in both temperature and velocity fields (Lakkaraju et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Boiling RB flow has been numerically simulated in recent years [66][67][68][69][70][71]. The simulations consider RB convection as the reference flow and compare several aspects of it with the 2-phase flow.…”
Section: Vapor-bubble Nucleation In Rayleigh-bénard Flowmentioning
confidence: 99%
“…[66][67][68][69][70][71]. In these studies a constant number of deliberately introduced bubbles (bubble nucleation and detachment was not simulated), with arbitrarily chosen diameters of several tens of µm, was seen to significantly change the structure of the convective flow.…”
Section: Introductionmentioning
confidence: 99%